1986
DOI: 10.1021/jf00069a037
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of rabbit serum arylester hydrolase

Abstract: Arylester hydrolase has been partially purified from rabbit serum to a specific activity matching or exceeding all previous reports. Calcium ion is absolutely required for activity. The widely reported rapid loss of arylester hydrolase activity was overcome by combining this Ca2+ requirement with the presence of 0.02% sodium azide. A method has also been devised to store the enzyme for long periods of time (years). During size exclusion chromatography, the enzyme behaved as if it had a molecular weight of 180-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Their molecular weight estimates as well as those reported here are in reasonable agreement with a molecular weight of 39617 calculated from the deduced human paraoxonase sequence without allowance for contribution from glycosylation (Hassett et al, 1991). Zimmerman and Brown (1986) reported the presence of two closely spaced bands of 40 000-45 000 and 47 000-54 000 in partially purified rabbit preparations, in agreement with the size of the denatured rabbit paraoxonase that we have observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Their molecular weight estimates as well as those reported here are in reasonable agreement with a molecular weight of 39617 calculated from the deduced human paraoxonase sequence without allowance for contribution from glycosylation (Hassett et al, 1991). Zimmerman and Brown (1986) reported the presence of two closely spaced bands of 40 000-45 000 and 47 000-54 000 in partially purified rabbit preparations, in agreement with the size of the denatured rabbit paraoxonase that we have observed.…”
Section: Discussionsupporting
confidence: 91%
“…Many attempts have been made to purify serum paraoxonase; however, purification to homogeneity has proven difficult, probably because paroxonase is intimately associated with the high-density lipoprotein complex (Kitchen et al, 1973;Don et al, 1975; Mackness et al, 1985; Zimmerman & Brown, 1986). Recently, Gan et al (1991) reported the purification of human paraoxonase to homogeneity.…”
mentioning
confidence: 99%
“…Similar results have been reported in both insects [11] and mammals [29,32]. In addition, the metal chelator EDTA significantly decreased PTEH activity in the bud moth from 58.0 to 28.33 pmol of methyl paraoxon hydrolyzed min ‫1מ‬ mg protein ‫1מ‬ (Figure 6).…”
Section: Inhibitors and Activation Of Phosphoric Triester Hydrolase Asupporting
confidence: 86%
“…Main [28] partially purified an enzyme from sheep serum with a molecular weight of 35,000 to 50,000. Furlong et al [26] purified phosphoric triester hydrolases from rabbit and human serum that were 35,000 and 38,000, respectively, and Zimmerman and Brown [29] purified an enzyme from rabbit serum that had arylesterase activity and estimated the molecular weight to be 180,000 to 200,000. Konno et al [11] estimated the molecular weight of the phosphoric triester hydrolase partially purified from the tobacco budworm to be approximately 120,000 by gel filtration.…”
Section: Purification Of Phosphoric Triester Hydrolasementioning
confidence: 99%